2017
DOI: 10.1513/annalsats.201704-297ws
|View full text |Cite
|
Sign up to set email alerts
|

An Official American Thoracic Society Workshop Report: Chemical Inhalational Disasters. Biology of Lung Injury, Development of Novel Therapeutics, and Medical Preparedness

Abstract: This report is based on the proceedings from the Inhalational Lung Injury Workshop jointly sponsored by the American Thoracic Society (ATS) and the National Institutes of Health (NIH) Countermeasures Against Chemical Threats (CounterACT) program on May 21, 2013, in Philadelphia, Pennsylvania. The CounterACT program facilitates research leading to the development of new and improved medical countermeasures for chemical threat agents. The workshop was initiated by the Terrorism and Inhalational Disasters Section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 153 publications
0
29
0
Order By: Relevance
“…In humans, isolated cases of accidental inhalation of high concentrations of Br 2 have reported respiratory and myocardial injury, cardiac arrest, and circulatory collapse (40,43). However, systematic studies on effects of Br 2 inhalation are recently emerging (1,5,17,28,31,32,48,58,67,71). The National Research Council has put forth a LD 50 for mice at an exposure of 204 parts per million (ppm) Br 2 for 30 min, and human studies have shown eye and throat irritation at 1-ppm exposure for up to 8 h (44a).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, isolated cases of accidental inhalation of high concentrations of Br 2 have reported respiratory and myocardial injury, cardiac arrest, and circulatory collapse (40,43). However, systematic studies on effects of Br 2 inhalation are recently emerging (1,5,17,28,31,32,48,58,67,71). The National Research Council has put forth a LD 50 for mice at an exposure of 204 parts per million (ppm) Br 2 for 30 min, and human studies have shown eye and throat irritation at 1-ppm exposure for up to 8 h (44a).…”
Section: Introductionmentioning
confidence: 99%
“…Additional therapies of potential benefit include inhaled betaagonists and N-acetylcysteine, as well as ibuprofen. 37,38,[43][44][45] After phosgene exposure, bed rest and close observation are recommended, with oxygen supplementation delayed until it is clinically required to prevent hypoxemia. If oxygen therapy is necessary, it should target oxygen saturation at the low end of the normal range in order to mitigate oxidant-induced injury.…”
Section: Primary Respiratory Irritantsmentioning
confidence: 99%
“…43,44 Delayed or persistent effects of respiratory irritants include airway hyperreactivity, or reactive airways dysfunction syndrome, characterized by acute bronchoconstrictor responses to otherwise innocuous concentrations of inhaled agents, 46,47 as well as interstitial pulmonary fibrosis, emphysema, bronchiectasis, and bronchiolitis obliterans. 37,39,45…”
Section: Primary Respiratory Irritantsmentioning
confidence: 99%
“…Of the 71 persons hospitalized for acute health effects because of Cl 2 exposure, one died in the hospital and 25 (35%) were admitted to intensive care, with a median length of stay of 3 days 15 . The number of hospital admissions for pulmonary and nonpulmonary causes subsequently increased significantly following the release of Cl 2 in South Carolina 16 . Eight‐ to 10‐months after the Graniteville incident cough and shortness of breath were still persistent in victims 17 .…”
Section: Introduction and Purposementioning
confidence: 99%
“…Patients who survive ALI from any source often develop chronic lung disease with airflow obstruction, fibrosis, 18 AHR, and impaired gas exchange 14,19–21 . These patients often require hospitalization 6,16 and are predisposed to bacterial infections 22 . AHR, also termed reactive airways dysfunction syndrome, has also been reported in individuals exposed to Cl 2 , and asthma‐like symptoms can persist for long periods 15,23 …”
Section: Introduction and Purposementioning
confidence: 99%